Analisis Perencanaan Pembangunan Ekonomi Berkelanjutan Kababupaten Dhamasraya - Hadinata, Ario Hernest; Putri Hanifa (Indonesia Economic Journal, 2025)
This study analyzes sustainable economic development planning located in Dhamasraya Regency, West Sumatra Province. This study uses a qualitative descriptive approach, this study utilizes secondary data from regional planning documents and official statistics to illuminate socio-economic conditions, education, economic growth, inequality, and demographics during the period 2020–2024. The results of this study show a positive trend in economic growth, decreasing poverty rates, and increasing the human development index (HDI) and the level of education participation in Dhamasraya Regency, but there are challenges in the form of increasing income inequality (gini ratio), the proportion of the population who are not/have not attended school is quite high, and there is pressure on basic services caused by population growth. Therefore, the direction of the planning can be suggested to include equalizing development results, improving the quality of human resources, strengthening leading economic sectors, managing population growth, and participatory government governance. This study also emphasizes the importance of an inclusive and sustainable development strategy in order to improve people's welfare evenly in the future.